Arthur, Origins, Identities and the Legendary History of Britain - Blacker, Jean, author.
1 online resource (672 pages)
Keywords: Geoffrey of Monmouth's immensely popular Latin prose Historia regum Britanniae (c. 1138), followed by French verse translations - Wace's Roman de Brut (1155) and anonymous versions including the Royal Brut , the Munich, Harley, and Egerton Bruts (12th -14th c.), initiated Arthurian narratives of many genres throughout the ages, alongside Welsh, English, and other traditions. Arthur, Origins, Identities and the Legendary History of Britain addresses how Arthurian histories incorporating the British foundation myth responded to images of individual or collective identity and how those narratives contributed to those identities. What cultural, political or psychic needs did these Arthurian narratives meet and what might have been the origins of those needs? And how did each text contribute to a "larger picture" of Arthur, to the construction of a myth that still remains so compelling today?